Stellarioides chartacea (Hyacinthaceae, Ornithogaloideae), a new species from the Eastern Cape Province in South Africa - Martínez-Azorín, Mario; Crespo, Manuel B.; Dold, Anthony P. (Phytotaxa, 2013)
Within the framework of a taxonomic revision of the genus Stellarioides we here describe a new species from the Eastern Cape Province in South Africa. Stellarioides chartacea sp. nov. is at first sight related to S. arida and S. tenuifolia, but it can be clearly differentiated by a number of characters. A complete description is presented for this species, and data on morphology, ecology, and distribution are reported. Affinities and divergences with other close allies are also discussed.